2021
DOI: 10.1101/2021.12.01.21267147
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparison of Saliva and Mid-Turbinate Swabs for Detection of COVID-19

Abstract: BackgroundSaliva is an attractive sample for detecting SARS-CoV-2 because it is easy to collect and minimally invasive. However, contradictory reports exist concerning the sensitivity of saliva versus nasal swabs.MethodsWe recruited and followed close contacts of COVID-19 cases for up to 14 days from their last exposure and collected self-reported symptoms, mid-turbinate swabs (MTS) and saliva every two or three days. Ct values and frequency of viral detection by MTS and saliva were compared. Logistic regressi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 30 publications
2
16
0
Order By: Relevance
“…Most studies of SARS-CoV-2 viral loads used the nasal or nasopharyngeal (NP) swab sample collection method [5][6][7]. The viral load in saliva and oral swab samples has been correlated with COVID-19 symptoms and transmissibility, and have been suggested to be similarly or slightly more sensitive than nasal swabs early in the infection cycle [8][9][10][11][12][13][14]. Low Ct values are associated with high viral load and increased transmissibility, primarily due to viral presence in saliva droplets that facilitate spread when infected individuals are in proximity [7,[15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Most studies of SARS-CoV-2 viral loads used the nasal or nasopharyngeal (NP) swab sample collection method [5][6][7]. The viral load in saliva and oral swab samples has been correlated with COVID-19 symptoms and transmissibility, and have been suggested to be similarly or slightly more sensitive than nasal swabs early in the infection cycle [8][9][10][11][12][13][14]. Low Ct values are associated with high viral load and increased transmissibility, primarily due to viral presence in saliva droplets that facilitate spread when infected individuals are in proximity [7,[15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Besides the obvious advantage of self-collection associated with lower costs and reduced risks for viral transmission, 8, 10 raw saliva samples can be processed directly through RT-qPCR assays which reduces time and removes costs associated with RNA extraction. In addition, saliva (through droplets and aerosols) constitutes a transmission route for SARS-CoV-2 infection and can contain high viral loads of infectious virus as reported by recent studies 7,11,12,22 . Thus, direct testing for SARS-CoV-2 in saliva can help monitor viral loads across variant surges and assess risk of transmission.…”
Section: Discussionmentioning
confidence: 95%
“…In addition to structural differences between variants at the nucleic or polypeptide levels, the viral load and clearance across tissues and disease stages can potentially differ between variants which in turn could have an impact on what biological specimens are most suitable for detecting different variants. Indeed, the omicron SARS-CoV-2 variant poses a significant challenge for nasal swab based testing as there are indications that saliva based samples may be more effective for diagnostic detection of the omicron SARS-CoV-2 variant relative to NSPs 12, 22 . Marais et al .…”
Section: Discussionmentioning
confidence: 99%
“…Nasopharyngeal swab, anterior-nares swab, mid-turbinate swab, oropharyngeal swab, buccal swab, gingival crevicular fluid, sputum, tracheal aspirate, and saliva have all been put forth and compared as diagnostic specimens for the detection of SARS-CoV-2 infection. Work done by many groups, 3-5 including ours 6 , has suggested that SARS-CoV-2 is detectable, albeit at low viral loads, in saliva before anterior nares nasal-swab samples. However, conflicting results have been reported in head-to-head comparisons of saliva to other specimen types in cross-sectional studies.…”
Section: Introductionmentioning
confidence: 92%